Persepsi Peserta Didik Terhadap Penggunaan Teknologi Pembelajaran Pada Mata Pelajaran Seni Budaya di Sekolah Menengah Kejuruan Negeri 2 Kupang - Taneo, Dersy Rejoice; Ratu, Steffi Eka Permatasari R. A.; Lodang, Dermawati R. W. (Metta : Jurnal Ilmu Multidisiplin, 2024)
This study aims to reveal students' perceptions of the use of learning technology in the subject of Arts and Culture at State Vocational High School 2 Kupang. The research method used is descriptive qualitative with data collection through observation, interviews, and documentation. The results of the study indicate that most students have a positive perception of the use of learning technology. Students feel more interested, motivated, and easy to understand learning materials. However, there are several obstacles encountered, such as limited access to technology and lack of teacher skills in using technology. This study concludes that the use of learning technology has great potential to improve the quality of Arts and Culture learning at State Vocational High School 2 Kupang. The effectiveness of the use of technology in the context of arts and culture learning and provides recommendations for teachers and schools in integrating technology optimally. The main challenges in the use of learning technology are the lack of adequate infrastructure, lack of training for teachers, and lack of variation in the use of technology. To overcome these challenges, efforts need to be made to improve technological infrastructure, ongoing training for teachers, and the development of more varied technology-based learning materials.